DDRE-10. SCREENING OF EPIGENETIC COMPOUNDS IN GLIOMA AND GLIOBLASTOMA IDENTIFIES NOVEL THERAPEUTICS FOR THEIR POTENTIAL TREATMENT. (12th November 2021) - Tatman, Philip; Wroblewski, Tadeusz; Fringuello, Anthony; Scherer, Sam; Foreman, William; Damek, Denise; Youssef, Samy; Lillehei, Kevin; Ormond, David; Graner, Michael
Abstract: BACKGROUND: 28% of primary central nervous system tumors are glioma and glioblastoma. These tumors are responsible for 80% of malignant brain neoplasms and most brain tumor related deaths. Despite modern therapies, patients with grade II gliomas have an average survival of 8-15 years, while patients with grade III tumors have an average survival of 3-5 years, and patients with glioblastoma have an average survival of 12-15 months. The lack of a curative treatment for this group of tumors supports additional research and novel approaches to identify more effective therapies. METHODS: In this study, we developed a high-throughput drug screen and culture system to identify epigenetic inhibitor compounds with the potential to reduce glioma and glioblastoma viability. RESULTS: We screened 33 tumors: 18 glioblastoma, 8 oligodendroglioma, and 7 astrocytoma. The top three most effective compounds across the full glioma cohort were all HDAC inhibitors; in order from most effective: panobinostat (average tumor viability = 52.5% +/-14.1SD; p=2.16x10 -61 ), LAQ824 (average tumor viability = 58.1% +/-18SD; p=1.48x10 -45 ), and HC Toxin (average tumor viability = 64% +/-21.1SD; p= 1.16x10 -33 ). Additionally, HDAC inhibition was also the most effective across each histopathological glioma type: astrocytoma, oligodendroglioma, and glioblastoma. UNC0631(G9a inhibitor) and JIB-04(KDM inhibitor) were the most effective compounds in the six recurrent tumors, though HDAC inhibition was still significantly effective in this group. We also evaluated drug sensitivity with respect to tumor grade, prior treatment, de novo vs progressive etiology, EGFR amplification, IDH mutation, MGMT methylation, and patient gender. CONCLUSIONS: After screening a large glioma cohort against a panel of epigenetic inhibitors, we found HDAC inhibition most effectively reduced tumor viability across all histopathological types and grades. These findings require further in vivo validation.